STRATEGI KOMUNIKASI PEMASARAN EVENT ORGANIZER PT. TIGA PRODUCTION DALAM MENDAPATKAN KEPERCAYAAN PELANGGAN (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
Based on the research results, it can be concluded that the marketing communication strategy adopted by PT. Tiga Production uses the Marketing Communication Mix application pattern which includes Public Relations, carrying out various programs related to the client or the community, Personal Selling interacting directly with the client by way of presentation and exchanging information, Advertising (Advertising) using social media Instagram, Webpages and Facebook as a medium for promotion and dissemination of information, and Sales Promotion (Sales Promotion) held a press conference by inviting local media partners and online portal reporters to cover the event. As well as using the theory of SWOT analysis which aims to determine the strengths and weaknesses of PT. Tiga Production in taking advantage of opportunities and reducing the impact of external threats. Even so, the four strategies above were carried out in establishing cooperation between PT. Tiga Productions and customers have experienced obstacles in communicating, this is due to several factors, namely: (1) Knowledge Gap regarding events, (2) Difficulty in convincing clients of an idea offered and (3) Internal processes from clients that often interfere with the timeline work from EO. The implications of this research are: (a) It is expected that PT. Tiga Production to be active in conducting intensive publishing activities by utilizing the development of new media in developing websites and supporting advertising in the mass media so that promotions can be conveyed to the public as a whole. (b) It is hoped that this research can become a reference in running a business in the service sector in gaining customer credibility and useful for students who wish to complete similar final assignments.